Does problem-based learning increase accounting students' critical thinking and learning outcomes? - Nurhasanah, Nurhasanah; Ahman, Eeng; Dahlan, Dadang; Mulyadi, Hari (Universitas Pamulang, 2025)
This study examines the impact of implementing a problem-based learning (PBL) model on accounting students' critical thinking and learning outcomes. The design of this study was a quasi-experimental non-equivalent group pre-test and post-test involving 80 accounting students at Wahidin Vocational High School, Cirebon City. The pre-test and post-test results were then tested using the two-group sample t-test and paired t-test methods to test our hypotheses. As a result, we found that the PBL model improved critical thinking and student learning outcomes. In implementing the PBL model, we employed 10 learning steps, from identifying learning objectives, designing problems, encouraging students to research and find solutions to problems, and contextualizing learning outcomes. Finding solutions to problems has proven effective in building critical thinking and student learning outcomes. The discussion process between students when building the right solution to the problem can also build a better understanding and competence in the accounting field. However, teachers need to be facilitators who can encourage student participation in finding solutions and discussions. Abstrak Studi ini menguji dampak implementasi model problem-based learning (PBL) terhadap critical thinking dan learning outcome siswa jurusan akuntansi. Desain penelitian ini adalah quasi-eksperimental non equivalent group pretest and postest yang melibatkan 80 siswa jurusan akuntansi di Sekolah Menengah Kejuruan Wahidin Kota Cirebon. Hasil dari pre-test dan post-test tersebut kemudian diuji dengan metode t-test two group sample dan paired t-test untuk menguji hipotesis yang dibangun. Hasilnya, penelitian ini menemukan bahwa model PBL terbukti dapat meningkatkan critical thinking serta learning outcome siswa. Dalam mengimplementasikan model PBL, kami menggunakan 10 langkah pembelajaran dari mulai mengidentifikasi tujuan pembelajaran, mendesain masalah, mendorong siswa untuk meneliti dan menemukan solusi atas masalah, hingga mengintegrasikan hasil pembelajaran secara kontekstual. Proses pencarian solusi atas masalah yang diberikan terbukti efektif dalam membangun critical thinking dan learning outcome siswa. Proses diskusi antar siswa ketika membangun solusi yang tepat atas masalah yang diberikan juga dapat membangun pemahaman dan kompetensi pada bidang akuntansi yang lebih baik. Hanya saja, guru perlu menjadi fasilitator yang dapat mendorong partisipasi siswa dalam proses pencarian solusi dan diskusi tersebut.